2007
DOI: 10.1080/13550280701327038
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus type 1 RNA Levels in different regions of human brain: Quantification using real-time reverse transcriptase–polymerase chain reaction

Abstract: Human immunodeficiency virus type 1 (HIV-1) enters the central nervous system shortly after the infection and becomes localized in different regions of the brain, leading to various neurological abnormalities including motor disorders and neurocognitive deficits. Although HIV-1-associated functional abnormalities of the central nervous system (CNS) can be evaluated during life by using various test batteries, HIV-1 virus concentration in different brain regions can be measured only after death. The tissues obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(107 citation statements)
references
References 68 publications
5
100
1
1
Order By: Relevance
“…With regard to the caudate nucleus, neurocognitive impairment was correlated with volume reduction and reduced blood flow [35]. Furthermore, virus accumulation together with decreased dopamine levels is present within the caudate nucleus [36,37].…”
Section: Motor Functionmentioning
confidence: 97%
“…With regard to the caudate nucleus, neurocognitive impairment was correlated with volume reduction and reduced blood flow [35]. Furthermore, virus accumulation together with decreased dopamine levels is present within the caudate nucleus [36,37].…”
Section: Motor Functionmentioning
confidence: 97%
“…Findings from several studies suggest that in the absence of opportunistic infections, HIV-1-associated neuronal loss found in different brain regions is a consequence of neuronal damage caused by the virus-related neurotoxins (Nath 2002), as well as the neurotoxic products generated by the infected extra-neuronal cells, including microglia and macrophages, and to some extent by astrocytes (Heyes et al 1991;Brabers and Nottet 2006;Anderson et al 2002;Brack-Werner 1999;Kaul and Lipton 2006). Recent studies by our group reported varying levels of HIV-1 RNA in different regions of postmortem brains with high concentration found in different nuclei of the basal ganglia, including the caudate nucleus, putamen, globus pallidus, and substantia nigra as well as in the fronto-cortical areas (Kumar et al 2007). Since these subcortical regions are also rich in dopaminergic activity and neurotoxicity of the dopaminergic system has been associated with AIDS dementia (Nath et al 2000), we propose that high levels of HIV-1 RNA found in these brain regions may be responsible for inducing the higher production of neurotoxins that result in the loss of dopaminergic neurons and a decrease in the availability of dopamine, leading to impairment in neuromotor and neurocognitive functions in individuals with HIV-1 infection.…”
Section: Introductionmentioning
confidence: 92%
“…HIV-1 gp41-positive microglia were most numerous in globus pallidus obtained from the brain of AIDS encephalitis patients [27]. Relatively higher levels of HIV-1 RNA were found in dopamine-rich parts of human brain samples (substantia nigra, caudate nucleus, basal ganglia, and globus pallidus) obtained at autopsy [17,28]. Overall, these data suggest that while HIV infection can generally cause brain atrophy, "dopamine-rich" areas can show proportionally more atrophy, suggesting a propensity for HIV in targeting these brain areas.…”
Section: Hiv/aids and Brain Pathology In Dopamine-rich Areasmentioning
confidence: 99%